pBaSysBioII: an integrative plasmid generating gfp transcriptional fusions for high-throughput analysis of gene expression in Bacillus subtilis. - DEVINE, KEVIN (My University, 2010)
Plasmid pBaSysBioII was constructed for high-throughput analysis of gene expression in Bacillus subtilis. It is an integrative plasmid with a ligation-independent cloning (LIC) site, allowing the generation of transcriptional gfpmut3 fusions with desired promoters. Integration is by a Campbell-type event and is non-mutagenic, placing the fusion at the homologous chromosomal locus. Using phoA, murAA, gapB, ptsG and cggR promoters that are responsive to phosphate availability, growth rate and carbon source, we show that detailed profiles of promoter activity can be established, with responses to changing conditions being measurable within 1 min of the stimulus. This makes pBaSysBioII a highly versatile tool for real-time gene expression analysis in growing cells of B. subtilis.
PUBLISHED
Keywords: Bacillus subtilis.